Model for superconductivity in optimally doped electron cuprates - Geballe, T.H.; Moyzhes, B.Y. (Физика низких температур, 2001)
The very anomalous

normal state properties and superconductivity of electron-doped supercon-ducting cuprates

with the T* structure are discussed. The literature values of high mobilities for electrons

and holes are explained by the electrons and holes existing in different layers. The

annealing procedures necessary for superconductivity produce oxygen-vacancy negative-U

pairing centers. The relative insensitivity of Tc to the annealing condition is attributed

to stabilization of the chemical potential near the middle of the narrow oxygen band formed

by oxygen vacancies where the electronic entropy is large.